Hutang Bersyarat Dalam Bentuk Pemberian Modal Pada Sektor Pertanian Perspektif Etika Bisnis Islam - Miftah Falahul Aqil (Institute of Research and Community Service at Islamic University of Bunga Bangsa Cirebon, 2021)
This receivable is a contract that aims to help, not as capital development. So that the additional conditions set by the receivable are not allowed. The practice of debt and credit carried out by the people of Karangsong Village is conditional debt. This practice of debt and credit has been carried out by the local community for a long time. With the guarantee of rice fields ownership and using a belief system, so that the implementation of accounts payable is very accessible compared to borrowing money from financial institutions. Seeing the problems that occur, researchers are interested in examining the main problem as follows: how is the conditional debt in providing capital in the agricultural sector with the perspective of Islamic business ethics in Karangsong Village, Indramayu Regency? Sources of data in this study use primary data and secondary data sources. Data collection techniques using interviews and documentation. Interviews were conducted with investors and farmers. Meanwhile, the documentation was carried out in the village of Karangsong Village, Indramayu district. All of the data is analyzed qualitatively with the inductive thinking method. Based on the research that has been conducted in Desa Karangsong, Indramayu Regency, it can be seen that where the capital provider provides capital loans to farmers on the condition that the harvest from the farmer is sold to the capital provider and gives a discount per kilos of the harvest. Supposedly, in giving capital or debt to farmers, it is not because they only want to make profits, but must prioritize Islamic business ethics in accordance with Islamic law. So that neither party feels disadvantaged. Thus the practice of conditional debt in Karangsong Village, Indramayu Regency is not in accordance with the principles of Islamic business ethics, namely the principles of divine values, helping, and the value of justice. So that neither party feels aggrieved.. Abstrak Hutang piutang ini merupakan sebuah akad yang bertujuan untuk tolong-menolong, bukan sebagai pengembangan modal. Sehingga syarat tambahan yang ditetapkan pihak piutang itu tidak diperbolehkan. Praktek hutang piutang yang dilakukan oleh masyarakat Desa karangsong adalah hutang bersyarat. Praktik hutang piutang ini sudah cukup lama dilakukan oleh masyarakat setempat. Dengan jaminan kepemilikan sawah dan menggunakan sistem kepercayaan, sehingga pelaksanaan hutang piutang sangat mudah diakses dibandingkan meminjam uang di lembaga keuangan. Melihat permasalahan yang terjadi peneliti tertarik untuk meneliti pokok masalahnya sebagai berikut: bagaimana hutang bersyarat dalam pemberian modal pada sektor pertanian perspektif etika bisnis Islam di Desa Karangsong kabupaten indramayu?Adapun jenis penelitian adalah penelitian lapangan (field research). Sumber data dalam penelitian ini menggunakan data primer dan sumber data sekunder. Teknik pengumpulan data menggunakan wawancara dan dokumentasi. Wawancara dilakukan kepada pemberi modal dan petani. Sedangkan dokumentasi dilakukan di Desa Desa Karangsong kabupaten indramayu. Semua data tersebut dianalisis secara kualitatif dengan metode berpikir induktif.Berdasarkan penelitian yang telah dilakukan di Desa Desa Karangsong kabupaten indramayu dapat diketahui bahwa dimana pemberi modal memberikan pinjaman modal kepada petani dengan syarat hasil panen dari petani tersebut dijual kepada si pemberi modal dan memberikan potongan harga per kilo dari hasil panennya. Seharusnya dalam melakukan pemberian modal atau hutang kepada petani bukan karena semata-mata ingin mencari keuntungan saja, tetapi harus mengedepankan etika bisnis Islam yang sesuai dengan syariat Islam. Sehingga tidak ada salah satu pihak yangmerasa dirugikan. Dengan demikian praktik hutang bersyarat di Desa Karangsong kabupaten indramayu belum sesuai dengan prinsip-prinsip etika bisnis Islam yaitu prinsip nilai ketuhanan, tolong-menolong, dan nilai keadilan. Sehingga tidak ada salah satu pihak yang merasa dirugikan.